Representation of Ideology in Criminal News Texts About Children in Online Media: A Critical Discourse Analysis by Roger Fowler - Nurhidayah Nurhidayah; Muhammad Saleh; Syamsudduha Syamsudduha (Asian Journal of Social and Humanities, 2023)
Study This is qualitative descriptive research using a categorized critical paradigm in critical discourse analysis research which aims to: (1) reveal representation ideology in text news criminal child on media online based on the aspect of vocabulary. (2) reveal ideological representations in the text news criminal child on media online based on aspect system language. Data This research is the words, clauses, and sentences contained in criminal news ideological representation of critical discourse analysis theory by Roger Fowler. Data source in study This is media online SINDOnews.com. As for technique collection data which done is documentation, reading techniques, and techniques note. The data analysis technique in this study includes four stages, namely data reduction, data presentation, verification, and drawing conclusions using Roger Fowler's critical discourse analysis. The results of the research show that: (1) ideological representation in news texts criminal child on aspect vocabulary modality found four vocabulary and classification (term new) found ten vocabularies on media online SINDOnews.com. (2) representation ideology in text news In the aspect of passive grammar, ten vocabularies and nominalization grammar were found ten vocabulary in the media online SINDOnews.com